2019
DOI: 10.1177/0363546519829034
|View full text |Cite
|
Sign up to set email alerts
|

Are Amniotic Fluid Products Stem Cell Therapies? A Study of Amniotic Fluid Preparations for Mesenchymal Stem Cells With Bone Marrow Comparison

Abstract: Background: In vivo amniotic fluid is known to contain a population of mesenchymal stem cells (MSCs) and growth factors and has been shown to assist in healing when used as an adjunct in procedures across multiple medical specialties. It is unclear whether amniotic fluid products (AFPs) contain MSCs and, if so, whether the cells remain viable after processing. Purpose: To determine whether MSCs, growth factors, and hyaluronan are present in commercially available AFPs. Study Design: Descriptive laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 29 publications
(50 reference statements)
0
21
0
Order By: Relevance
“…Since these cells have not been culture expanded, they do not meet the ISCT criteria for an MSC population and should not be referred to as “mesenchymal stem cells.” A recent independent analysis of 3 commercially available amniotic fluid products found that none formed any CFUs in culture, confirming the absence of any MSCs in these products. 11 Most of the commercially available cell formulations derived from placental and amniotic tissues are poorly characterized and currently lack rigorous analysis of the cell content and biologic activity. These materials are often marketed as “stem cell” preparations, which they clearly are not.…”
Section: Placenta Umbilical Cord Blood and Amniotic Tissuesmentioning
confidence: 99%
“…Since these cells have not been culture expanded, they do not meet the ISCT criteria for an MSC population and should not be referred to as “mesenchymal stem cells.” A recent independent analysis of 3 commercially available amniotic fluid products found that none formed any CFUs in culture, confirming the absence of any MSCs in these products. 11 Most of the commercially available cell formulations derived from placental and amniotic tissues are poorly characterized and currently lack rigorous analysis of the cell content and biologic activity. These materials are often marketed as “stem cell” preparations, which they clearly are not.…”
Section: Placenta Umbilical Cord Blood and Amniotic Tissuesmentioning
confidence: 99%
“…Mid-trimester and term human amniotic fluid stem cells (hAFSCs) are available in large quantities and have been well characterized as multipotent cells that can be a resource for clinical transplantation and allow their future therapeutic use as an ''off-the-shelf'' cell source in regenerative medicine. 8,9 hAFSCs collected during pregnancy were demonstrated to have remarkable plasticity, and immunomodulatory effects and have the potential for the treatment of various diseases especially in neonates when autologous cell therapy is required; even immediately after birth. 5,9 They also have a pluripotent potential property identical to embryonic stem cells (ESCs) or induced pluripotent stem cells (iPSCs) that can be reprogrammed to a pluripotency potential without any genetic manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…A recent, elegant study evaluated stem cells in amniotic fluid products and also showed that no live stem cells were identified in 3 tested products. 22 It is common that 1 or a limited number of cell surface/CD markers are used to identify MSCs in a product. A critical concept is that there is no single CD marker that will identify MSCs; a panel of markers, used simultaneously, is required to positively identify stem cells.…”
Section: Discussionmentioning
confidence: 99%